1996
DOI: 10.1128/mcb.16.11.5974
|View full text |Cite
|
Sign up to set email alerts
|

Basal Phosphorylation of the PEST Domain in IκBβ Regulates Its Functional Interaction with the c-rel Proto-Oncogene Product

Abstract: The NF-B/Rel family of transcription factors plays a critical role in the development of a normal immune response (39, 65, 75). The nuclear activities of NF-B/Rel proteins are regulated from the cytoplasmic compartment by interactions with a set of inhibitory proteins, including IB␣ and IB␤ (26,71,74). Cellular stimulation leads to the rapid degradation of these conditionally labile inhibitors and the transit of active NF-B/Rel complexes to the nucleus (9,26,74). Primary structural and functional analyses have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 73 publications
5
87
1
Order By: Relevance
“…We then examined the potential role of the Cterminal sequences in the degradation of IB␤. In this regard, the C-terminal portion of IB␤ is rich in serines and aspartic acids (12) and has recently been shown to contain the sites for constitutive phosphorylation (41). Consistent with this recent study, an IB␤ mutant lacking the C-terminal 51 amino acids {IB␤(1-308)} migrated on SDS-PAGE as a single band (lane 7), indicating the lack of constitutive phosphorylation.…”
Section: Tnf-␣ Promotes Calyculin A-induced Degradation Of Ib␤-supporting
confidence: 70%
“…We then examined the potential role of the Cterminal sequences in the degradation of IB␤. In this regard, the C-terminal portion of IB␤ is rich in serines and aspartic acids (12) and has recently been shown to contain the sites for constitutive phosphorylation (41). Consistent with this recent study, an IB␤ mutant lacking the C-terminal 51 amino acids {IB␤(1-308)} migrated on SDS-PAGE as a single band (lane 7), indicating the lack of constitutive phosphorylation.…”
Section: Tnf-␣ Promotes Calyculin A-induced Degradation Of Ib␤-supporting
confidence: 70%
“…This change may coincide with either greater or lesser sensitivity to specific inducing agents. In addition, it has been reported that IB␣ is controlled under some circumstances by tyrosine phosphorylation, which results in dissociation but not degradation (13,26). As discussed above, this mechanism is more tenable if the affinity of the complex is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…PLC-g1 antibody was obtained from Transduction Laboratories and used at a 1 : 1000 dilution. The p50, p65 and c-rel antibodies, plus pCMV4-IkBa(DN37) were generous gifts from Dr Bean Ballard (Vanderbilt University, Nashville, TN) and were previously described (Brockman et al, 1995;Chu et al, 1996).…”
Section: Reagentsmentioning
confidence: 99%